Clinical Outcomes of Patients with IMP-type Carbapenemase-Producing Enterobacteriaceae. (4th October 2017) - Hayakawa, Kayoko; Ishikane, Masahiro; Mezaki, Kazuhisa; Katanami, Yuichi; Takaya, Saho; Yamamoto, Kei; Kutsuna, Satoshi; Nagashima, Maki; Sugiki, Yuko; Ohmagari, Norio
Abstract: Background: Dominant molecular types of carbapenemase-producing Enterobacteriaceae (CPE) vary geographically. The clinical outcome of IMP-type CPE (IMP-CPE), the dominant type in Japan, is not well known. Methods: Non–meropenem-susceptible per CLSI criteria and/or ceftazidime-resistant Enterobacteriaceae were screened, and metallo-β-lactamase-positive isolates were examined for bla IMP by PCR. Unique IMP-CPE-positive cases (January 2012–December 2016) were included. Medical charts were reviewed retrospectively. Results: Enterobacter cloacae (EC) ( n = 67, 59.8%) were most frequently isolated followed by Klebsiella pneumoniae (KP) ( n = 31, 27.7%), Citrobacter freundii ( n = 4, 3.6%), and E. coli ( n = 4, 3.6%) among 112 IMP-CPE identified. Although 30-day mortality was slightly higher in KP, clinical outcomes and background factors were similar between KP and EC; isolation sites were significantly different ( P = 0.04). In 10 bacteremia cases, 1 of 9 (11.1%) EC patients died in hospital within 30 days. All CPE except 1 EC were sensitive to ≥1 of levofloxacin (LVFX), amikacin (AMK), or gentamicin (GM). GM resistance was more common in KP than in EC ( P < 0.01). Independent predictor for 30-day mortality was age adjusted Charlson Comorbidity Index (aCCI) ≥8 (adjusted odds ratio 6.4 [95% CI: 1.9-21.7], P = 0.003) in multivariate analysis controlled for species of CPE, and polymicrobial isolation. Conclusion: IMP-CPE had significant clinical impact on, and higher mortality in, the elderly population with multiple comorbid conditions. Disclosures: All authors: No reported disclosures.